KOMPARATIF TEKNIK DAN EKSPRESI DALAM SENI KRIYA - Suardana, I Wayan (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
In modern system fine arts discourse these days, expression and technique region is always questioned to assign value whether/what the masterpiece can category as swan song or not. Expression always made by ivorytower in creation of swan song of technique and always the attention cannot and considered to be skilled as supporter in course of the creation. Expression is even also comprehended and careful shallow/ superficially where swan song which is not borne with emotional emotion it is not the expressive masterpiece endless. Understanding confusion bear all discourse of confused which to isolate in the end swan song which adiluhung placedly at region of swan song of under because assumed less be expressive. Regionas discourse problem of expression and technique befall art kriya so that on the way nya artis tic [of] kriya have multifarious to mention of manner that is crafting/ diligence art craft artistic of artistic craft. This mention place art craft of at very region is corner. Very ironic once where art craft which adiluhung category as art of second class of because its birth is assumed only need mere crafmanshif and without carrying expression. Discourse mistake and have enter of at system discourse of fine arts by komfrehensif require to be straightened, so that domicile art become is equal to energy and material express different. Key word: kriya, crafmanshif, adiluhung